2020
DOI: 10.1245/s10434-020-08741-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Hepatic Perfusion with Melphalan in Patients with Unresectable Ocular Melanoma Metastases Confined to the Liver: A Prospective Phase II Study

Abstract: Background Ocular melanoma is the most common primary intraocular malignancy and has a very poor prognosis once liver metastases occur. The aim of this study was to prospectively assess the efficacy and safety of percutaneous hepatic perfusion with melphalan (M-PHP) using the new second-generation (GEN 2) hemofiltration system in patients with ocular melanoma metastases confined to the liver. Methods Prospective, single-center, single-arm, phase II study including patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
(50 reference statements)
3
23
0
2
Order By: Relevance
“…Our results suggested that the perioperative management of PHMP is frequently associated with procedure-related issues. These findings are in similarity with previous studies from other centers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The main issues related to PHMP were hemodynamic depression, vascular access complications, and coagulopathy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results suggested that the perioperative management of PHMP is frequently associated with procedure-related issues. These findings are in similarity with previous studies from other centers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The main issues related to PHMP were hemodynamic depression, vascular access complications, and coagulopathy.…”
Section: Discussionsupporting
confidence: 90%
“…Fifty-three PHMP procedures of 16 patients were analyzed. In all of the cases, procedurerelated hypotension required the median (range) highest noradrenaline infusion rate of 0.5 (0.17-2.1) μg kg min -1 and fluid resuscitation volume of 5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) liters. Eighty-four PHMPrelated complications were observed in 33 cases (62%), of which 9 cases (27%) involved grade III and IV complications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This prospective, phase II study investigated the efficacy and safety of M-PHP using the GEN 2 filter in well-selected patients with unresectable metastases from ocular melanoma confined to the liver. 5 Sixty-four M-PHP procedures were performed in 35 patients. The overall response rate of 72% (complete response 3%, partial response 69%) and median overall survival (OS) of 19.1 months in the current study appeared to be more favourable compared with published data on other treatment modalities and provide convincing evidence for the efficacy of M-PHP in metastatic ocular melanoma.…”
Section: Presentmentioning
confidence: 99%